2021
DOI: 10.1039/d1sc00986a
|View full text |Cite
|
Sign up to set email alerts
|

Deaminative meta-C–H alkylation by ruthenium(ii) catalysis

Abstract: Precise structural modifications of amino acids are of importance to tune biological properties or modify therapeutical capabilities relevant to drug discovery. Herein, we report a ruthenium-catalyzed meta-C–H deaminative alkylation with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 104 publications
0
9
0
2
Order By: Relevance
“…The power of ruthenium catalysis was reflected by a broad range of remote transformations, including alkylations, benzylations, carboxylations, formylations, acylations, sulfonylations, halogenations, and nitrations as well as very recent deaminative meta-C-H functionalizations. 80 Especially, the synthetic applications and late-stage modifications of bio-relevant compounds through ruthenium-catalyzed remote functionalizations have become more attractive to the chemical and pharmaceutical industries. In addition, ruthenium catalysis was effective for sequential meta-/ortho-C-H difunctionalizations with excellent levels of chemo-and site-selectivities.…”
Section: Discussionmentioning
confidence: 99%
“…The power of ruthenium catalysis was reflected by a broad range of remote transformations, including alkylations, benzylations, carboxylations, formylations, acylations, sulfonylations, halogenations, and nitrations as well as very recent deaminative meta-C-H functionalizations. 80 Especially, the synthetic applications and late-stage modifications of bio-relevant compounds through ruthenium-catalyzed remote functionalizations have become more attractive to the chemical and pharmaceutical industries. In addition, ruthenium catalysis was effective for sequential meta-/ortho-C-H difunctionalizations with excellent levels of chemo-and site-selectivities.…”
Section: Discussionmentioning
confidence: 99%
“…Our scope studies were expanded to include Katritzky salts derived from primary aliphatic amines (29, 31, 36-40, 42, 43), as well as electron-poor or heterocyclic benzylic amines (30,41,44), although these substrates required heating to 110 °C. The method is quite general, tolerating basic amines (39)(40)42), amides (32), esters (35)(36)(37)(38), Michael acceptors (41), acetals (36,38), protecting groups including Boc and tosyl (29,(36)(37)(38), and oxime ethers (43) as well as polyfunctionalities seen in drug molecules such as levofloxacin (33), Boclysine methyl ester (37) enoxolone (41), and fluvoxamine (43). 39 and 40 are matched molecular pairs of moclobemide and metoclopramide, respectively, wherein the nitrogen atom has been replaced by an oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we conducted a series of competition experiments with reported radical precursors for ruthenium catalysis (Scheme 2). [20] First, Katritzky salt was utilized and found that desired C ‐alkyl glycosides 4 and direct meta ‐deaminative alkylation product 6′ were not formed (Scheme 2a) [21] . Instead, three‐component addition product 6 was isolated in 85 % yield.…”
Section: Methodsmentioning
confidence: 99%
“…[20] First, Katritzky salt was utilized and found that desired C-alkyl glycosides 4 and direct meta-deaminative alkylation product 6' were not formed (Scheme 2a). [21] Instead, three-component addition product 6 was isolated in 85 % yield. Second, when the radical precursor 2-bromo-2,2-difluoroacetate was employed, the product 4 was not formed (Scheme 2b).…”
mentioning
confidence: 99%